Skull Fracture and Haemorrhagic Pattern in Cases of Fatal Blunt Trauma Head Injury Autopsied at Tertiary Healthcare Centre in Eastern Nepal - Sah, Bikash; Yadav, Bishwanath; Jha, Shivendra; Khan, Abdul Sami (Med Phoenix, 2018)
Background: Head injury is regarded as a main health problem that is a common cause of morbidities and mortalities and makes great demand to control and prevent it. For this, policy makers need to see the pattern of head injury and this study is done to describe the pattern. Methods: Hospital based, descriptive cross sectional study done on one year autopsy cases of fatal blunt trauma head injury which was 76 in which proportion of different types of head injuries, their causes and their distribution as per age, sex, and duration of survival were studied. Results: Skull-vault fractures were present in 57 (75%) cases in which most common type of fracture was linear fracture constituting 29(49.12%). 50% of the cases were with skullbase fracture in which the most common was of anterior cranial fossa fracture(60.5%). 56.34% of the victims were with subarachnoid haemorrhage (SAH) followed by subdural haemorrhage (SDH) and extradural haemorrhage (EDH). 6.6% victims were without any intracranial haemorrhage. Road traffic accident alone accounted for 71% of total blunt trauma causations of this fatal head injury. 70% cases were in age group from 11 to 50 years and 78.9% were male. 51.3% died at the spot. Conclusions: The research findings have shown that among the fatal blunt trauma head injury cases, skull vault fracture was present in 75% and skull base fracture was present in 50%. The most common intracranial haemorrhage was subarachnoid haemorrhage (56.34%) followed by subdural and extradural haemorrhage. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 71-74